Perendaman dalam GA3 dan Penyimpanan pada Suhu Rendah untuk Pematahan Dormansi Umbi Bawang Putih (Allium sativum L.) - Palupi, Endah Retno; Septianingrum, Chintya Dwi; Putri, Erianna Ayu Emkha; Qadir, Abdul (Jurnal Hortikultura Indonesia, 2021)
Garlic seed cloves is usually separated from previous cropping, and cannot be planted directly due to dormancy. This research was conducted at the Seed Storage and Testing Laboratory of the Department of Agronomy and Horticulture during November 2017 to April 2019. The research consisted of two experiments. The first experiment was aimed at determining the effective GA3 concentration for breaking the dormancy of garlic seed cloves (var Tawangmangu Baru). The experiment was arranged in completely randomized design with two factors, i.e. GA3 concentrations (0, 50, 100, dan 150 ppm) and storage conditions (ambient room/27±2 °C and refrigerator/9±1 °C), replicated 4 times. The second experiment was aimed at breaking the dormancy, and was arranged in completely randomized design with two factors, i.e. immersion solutions (water/control, 50 ppm GA3 and 1.5% KNO3) and storage conditions (ambient room/29±2 ˚C, RH 87±2%, air-conditioned room/19±1 ˚C, RH 60±1%, and refrigerator/7±1 ˚C, RH 77±3%). In both experiments the seed cloves were immersed in different solutions as treatments for 24 h prior to storage at various conditions. The immersion was repeated prior to germination test. The results showed that the dormancy period of garlic seed cloves was more than 22 weeks after harvest (WFH). GA3 at 50 ppm was effective for breaking the dormancy of garlic seed cloves. Immersion in 50 ppm GA3 for 24 h followed by storage in low temperature (6 – 10 ˚C) for 8 weeks was effective for breaking dormancy of garlic seed cloves aged 6 WFH. Keywords: germination, quiescence, refrigerator, vigor index